PENGEMBANGAN APLIKASI TATA TERTIB SEKOLAH BERBASIS WEB DENGAN TEKNOLOGI WHATSAPP API MENGGUNAKAN MODEL WATERFALL PADA SMPN 1 KEJAYAN - Maulidha Sukendro, Natasha; Setiyaningsih, Wiji; Lugis Purwanto, Hari (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2025)
SMPN 1 Kejayan uses the Microsoft Excel Macro application to support the school order process. In this application, it was found that there is no database system that can store all data for each school year. The absence of a database system that is able to store all data for each school year, the lack of connection between one data and another automatically hampers the administrative process and monitoring of student discipline, prone to data input errors, and inaccurate report data. Another problem is experienced by parents who do not know the progress of their children's order at school and letters that are still in hardcopy are sometimes not submitted by students to their parents, causing misunderstandings between parents and counseling teachers. Based on these problems, a web-based application was developed. into a web-based application with Whatsapp API technology. This order application was built using the codeigniter framework and using the Waterfall development model. From the results of research and testing that has been carried out on applications using User Acceptance Testing (UAT) results in an overall average of 86.84%, indicating that the order application that has been designed can help the administrative process and monitoring of the order at SMPN 1 Kejayan.